Short‐Term Efficacy and Safety of Torasemide and Furosemide in 366 Dogs with Degenerative Mitral Valve Disease: The TEST Study. (4th October 2017) - Chetboul, V.; Pouchelon, J.‐L.; Menard, J.; Blanc, J.; Desquilbet, L.; Petit, A.; Rougier, S.; Lucats, L.; Woehrle, F.; ,
Abstract : Background: Furosemide is the only loop diuretic recommended by the ACVIM consensus guidelines for treatment of congestive heart failure (CHF) in dogs related to degenerative mitral valve disease (DMVD). Torasemide is another potent loop diuretic with a longer half‐life and a higher bioavailability. Objectives: (1) To demonstrate that torasemide given once a day (q24h) is noninferior to furosemide given twice a day (q12h) for treating dogs with CHF; (2) and to compare the effect of the 2 drugs on the time to reach a composite cardiac endpoint "spontaneous cardiac death, euthanasia due to heart failure or CHF class worsening." Animals: A total of 366 dogs with CHF attributable to DMVD. Methods: Analysis of 2 prospective randomized single‐blinded reference‐controlled trials was performed. Dogs orally received either torasemide q24h (n = 180) or furosemide q12h (n = 186) in addition to standard CHF therapy over 3 months. The primary efficacy criterion was the percentage of dogs with treatment success assessed in each study. The time to reach the composite cardiac endpoint was used as secondary criterion in the overall population. Results: Torasemide was noninferior to furosemide ( P torasemide  −  P furosemide  = +7%; 95% CI [−8%; +22%] and P torasemide  −  P furosemide  = +1%; 95% CI [−12%; +14%], respectively, in Study 1 and Study 2). Torasemide (median dose = 0.24 mg/kg/d q24h; range = 0.10–0.69 mg/kg/d) was associated with a 2‐fold reduction in the risk of reaching the composite cardiac endpoint (adjusted HR = 0.47; 95% CI = 0.27–0.82; P  = 0.0077) as compared with furosemide (median dose = 1.39 mg/kg q12h; range = 0.70–6.30 mg/kg q12h). Conclusions and Clinical Importance: Torasemide q24h is an effective oral diuretic in dogs with CHF.